PENGAMATAN PENYEBARAN UNSUR RADIOAKTIF 131 32 RADIOIODINE ( I) DAN RADIOFOSFOR ( P) PADA TANAMAN JAGUNG DAN KEDELE - SENNY SUNANISARI (Research Center for Biology-Indonesian Institute of Sciences, 1988)
S. SUNANISARI. 1988.Otjervation on the distribution of radioactive elements tadioiodine (I )and radiophosphorous ( 32 P) in maize and soybean.Berita Biologi,3(8): 371 - 373.The plants are able to absorb nutrients from their environment either was carried out to natural in the form of particles or synthetic radioactives.This experiment check the absorbtion and distribution of the radio actives 1311 and 32p on maize and soybean.The1 absorbtion of these radioactives were influenced by some physical factors of the substrat.At sludge substratum,plants absorbed 32p more than 131l.The distribution of 32p and 1311 were checked by their accumulation on.the plant organs.In maize, the accumulation of 32p and 131I were started from root, followed by stem, and leaves,while in soybean, they were started from root, followed by stem, leaves and cotyledon.